-14-6(2x+1)=16

Simple and best practice solution for -14-6(2x+1)=16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -14-6(2x+1)=16 equation:


Simplifying
-14 + -6(2x + 1) = 16

Reorder the terms:
-14 + -6(1 + 2x) = 16
-14 + (1 * -6 + 2x * -6) = 16
-14 + (-6 + -12x) = 16

Combine like terms: -14 + -6 = -20
-20 + -12x = 16

Solving
-20 + -12x = 16

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '20' to each side of the equation.
-20 + 20 + -12x = 16 + 20

Combine like terms: -20 + 20 = 0
0 + -12x = 16 + 20
-12x = 16 + 20

Combine like terms: 16 + 20 = 36
-12x = 36

Divide each side by '-12'.
x = -3

Simplifying
x = -3

See similar equations:

| 2+4x=3x | | 15x^2-4x+7=0 | | -9=f+14 | | B+7.3=8.4 | | 4+2(m+3)=22 | | T-5.8=6.9 | | k^2+2k-9=0 | | 55=5a | | K+19=-12 | | F-23=15 | | 220-5=250-10x | | (1-2x)*(1-2x)=2.4x | | 10y=4 | | 10-3(2x-4)=-14 | | 3(2+n)=66 | | x^2+4x+-32=0 | | x^2+34x+437=0 | | 2(3+n)=28 | | 4x^2+1.6x+1=0 | | 220-5x=250-10x | | 3(5+n)=45 | | -y+1-3=-3 | | .8-7x=0 | | 7(n+4)=84 | | 3(3+n)=45 | | 4(x+5)=3(x+110) | | 12=4-3f+7 | | 2(7+n)=40 | | 3.7x-2.2=16.3 | | 1.62y=3.14(y-8.62) | | 5(2x-3)-6x=0.5(4x+10) | | 10m-50+20p=0 |

Equations solver categories